Teenagers’ knowledge of human sexuality and their views on teenage pregnancies - P. J. Kunene (Curationis, 1995)
There is concern about poor knowledge of human sexuality and a high rate of teenage pregnancies among Blacks. The primary aim of the study was to measure the knowledge that teenagers have on human sexuality and to identify the sources from which they obtain such knowledge. The secondary aim was to detect how teenagers perceive the teenage pregnancy problem and its consequences,